2017
DOI: 10.1016/j.neurobiolaging.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet and aging interact to produce neuroinflammation and impair hippocampal- and amygdalar-dependent memory

Abstract: More Americans are consuming diets higher in saturated fats and refined sugars than ever before, and based on increasing obesity rates, this is a growing trend among older adults as well. While high saturated fat diet (HFD) consumption has been shown to sensitize the inflammatory response to a subsequent immune challenge in young adult rats, the inflammatory effect of HFD in the already-vulnerable aging brain has not yet been assessed. Here, we explored whether short-term (3 days) consumption of HFD would serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
138
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(160 citation statements)
references
References 78 publications
(102 reference statements)
18
138
1
3
Order By: Relevance
“…On the one hand, MHC-fed rats showed increased expression of CD68 and IBA-1, both markers of microglial activation associated with chronic neuroinflammation(72), in the CA1 area of the hippocampus. On the other hand, increased apoptotic changes in MHC-fed rat hippocampus appeared as increased TUNEL staining and higher caspase-3 activity.Similar observations are common in recent literature whereby neuroinflammation and microglial activation(73)(74)(75), together with hippocampal apoptosis(76,77), occur in association with high fat diet-induced cognitive decline. The previous studies provided observational evidence for the aforementioned association.…”
supporting
confidence: 87%
“…On the one hand, MHC-fed rats showed increased expression of CD68 and IBA-1, both markers of microglial activation associated with chronic neuroinflammation(72), in the CA1 area of the hippocampus. On the other hand, increased apoptotic changes in MHC-fed rat hippocampus appeared as increased TUNEL staining and higher caspase-3 activity.Similar observations are common in recent literature whereby neuroinflammation and microglial activation(73)(74)(75), together with hippocampal apoptosis(76,77), occur in association with high fat diet-induced cognitive decline. The previous studies provided observational evidence for the aforementioned association.…”
supporting
confidence: 87%
“…The age at which rodents are exposed to diet-induced obesity may be a factor. For example, one study found significant effects of HFD on behavior in mice started on diet at 5 weeks of age, but not in animals started at 8 weeks [ 129 ], whereas another found behavioral impairments in response to HFD in aged but not young adult rats [ 130 ]. These studies suggest that the age at which exposure to HFD occurs may be important in determining whether behavioral deficits are observed.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity or excess body weight negatively correlates with cognitive function and with the volume of several brain regions including hippocampus [20,21]. In animal studies, high fat diet feeding induces neuroinflammation, which leads to the cognitive decline [22]. These findings suggest that preventing type II diabetes and obesity would be effective approaches in dementia prevention.…”
Section: Iaas Prevent Type II Diabetes Lipid Metabolism and Obesitymentioning
confidence: 98%